2019
DOI: 10.1088/1361-6528/ab4e46
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired growth of iron derivatives on mesoporous silica: effect on thermal degradation and fire behavior of polystyrene

Abstract: Aiming to investigate the influence of pore property of mesoporous material on thermal degradation and fire behavior of polystyrene (PS), the ultrafine iron derivatives were uniformly grown on the interior wall of SBA-15 via the coordination-induced assembly by bioinspired polydopamine (PDA). The resultant SBA-15@PDA@Fe was verified by various characterizations with the dominant component of FeOOH. Compared with PS composites with SBA-15, PS composites with SBA-15@PDA@Fe revealed the notably divergent alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…21 With the addition of synergists, IFR will possess excellent flame retardancy to avoid the problem of the deterioration of other properties of the material caused by the addition of a large amount of IFR. 22,23 In terms of IFR, the commonly used synergists mainly include carbon nanotubes (CNT), 24,25 zeolite molecular sieve, 26 organic montmorillonite (MMT), 27 halloysite (HNT), 28 metal oxides 29 and other substances. 30,31 Halloysite, an excellent natural IFR synergist, can accelerate the formation of the expansion char layer, increase the amount of carbon residue and make the carbon residue stable and dense by physically strengthening or producing aluminophosphate and chemical interaction with IFR.…”
Section: Introductionmentioning
confidence: 99%
“…21 With the addition of synergists, IFR will possess excellent flame retardancy to avoid the problem of the deterioration of other properties of the material caused by the addition of a large amount of IFR. 22,23 In terms of IFR, the commonly used synergists mainly include carbon nanotubes (CNT), 24,25 zeolite molecular sieve, 26 organic montmorillonite (MMT), 27 halloysite (HNT), 28 metal oxides 29 and other substances. 30,31 Halloysite, an excellent natural IFR synergist, can accelerate the formation of the expansion char layer, increase the amount of carbon residue and make the carbon residue stable and dense by physically strengthening or producing aluminophosphate and chemical interaction with IFR.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such predicament, a plentiful of halogen‐free organic flame retardants (phosphorus‐based, 3 boron‐based, 4 etc.) and nano‐fillers, including molybdenum disulfide (MoS2), 5 graphene oxide (GO), and multi‐walled carbon nanotube (MWCN), 6,7 polyhedral oligomeric silsesquioxane (POSS), 8 porous silicon, 9 carbon nitride (g‐C 3 N 4 ), 10 layered double hydroxide (LDH), 11 metal organic frameworks (MOFs) and MXene, 12,13 have been synthesized and fabricated and used to improve flame resistance of PS. Although fire spread inhibition and smoke suppression during combustion have been achieved in cone calorimeter test due to addition of these flame retardants, simultaneously obtaining self‐extinguishment and anti‐dripping abilities of PS composites in burning test remains a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon‐containing materials have been also used widely as eco‐friendly flame‐retardants with no phosphorus 44–51 . It has been reported that the presence of silicon element in a flame‐retardant material has improved the thermal stability of the char layer formed during combustion 44,48,50,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous silica materials, such as MCM‐41 and SBA‐15, are largely studied because of facile synthesis, ease of successive functionalization, highly ordered nanostructure, large surface area, and uniform and tailorable pore size 53,54 . Mesoporous silica‐based materials have attracted the attention of many researchers in the field of flame retardancy in recent years 44,45,51,55,56 . High surface area, uniform and large pore size, special open‐pore structure, and the presence of SiOH active sites make mesoporous silica more conducive to toxic smoke suppression and molecular capture.…”
Section: Introductionmentioning
confidence: 99%